2021
DOI: 10.1371/journal.pone.0248787
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of a potato (Solanum tuberosum L.) breeding collection for southern Colombia using Single Nucleotide Polymorphism (SNP) markers

Abstract: Detailed knowledge on genetic parameters such as diversity, structure, and linkage disequilibrium (LD) and identification of duplicates in a germplasm bank and/or breeding collection are essential to conservation and breeding strategies in any crop. Therefore, the potato genetic breeding collection at the Universidad de Nariño in Colombia, which is made up of diploid and tetraploid genotypes in two of the more diverse genebanks in the world, was analyzed with 8303 single nucleotide polymorphisms (SNP) from Sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…The LD mean value and the genetic diversity (Ho) of diploids contrasted with the values of the mixed and tetraploid populations. The same pattern of high LD and low Ho in diploid potatoes and low LD and high Ho in tetraploids was previously reported ( Berdugo-Cely et al., 2017 ; Berdugo-Cely et al., 2021 ). As reported in other studies ( Gebhardt et al., 2004 ; Simko et al., 2006 ), the LD decayed slowly in all populations, and it is explained by the clonal propagation of potatoes that limits the number of meiotic generations and, in consequence, the recombination events ( Gebhardt et al., 2004 ; Simko et al., 2006 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The LD mean value and the genetic diversity (Ho) of diploids contrasted with the values of the mixed and tetraploid populations. The same pattern of high LD and low Ho in diploid potatoes and low LD and high Ho in tetraploids was previously reported ( Berdugo-Cely et al., 2017 ; Berdugo-Cely et al., 2021 ). As reported in other studies ( Gebhardt et al., 2004 ; Simko et al., 2006 ), the LD decayed slowly in all populations, and it is explained by the clonal propagation of potatoes that limits the number of meiotic generations and, in consequence, the recombination events ( Gebhardt et al., 2004 ; Simko et al., 2006 ).…”
Section: Discussionsupporting
confidence: 88%
“…The CCC has a strong population structure based on the ploidy level; this collection is structured into diploid and tetraploid potatoes ( Berdugo-Cely et al., 2017 ). Ploidy levels have been reported as one of the main factors to explain the population structure in other potato collections ( Stich et al., 2013 ; Hardigan et al., 2015 ; Berdugo-Cely et al., 2021 ). Identifying the genetic structure of panels used in association mapping analyses is essential to eliminate false marker-traits associations influenced by genetic relationships and population structure tendencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In different population structure and genetic diversity studies of genebank collections of traditional cultivars and breeding programs germplasm of potato, the material has been discriminated following ploidy, taxonomy, and characteristics of breeding selection ( Hirsch et al., 2013 ; Berdugo-Cely et al., 2017 ; Hardigan et al., 2017 ; Deperi et al., 2018 ; Ellis et al., 2018 ; Pandey et al., 2021 ). In general, it is observed that the genetic diversity studies of germplasm obtained from genebanks have shown that the discrimination among accessions is mainly associated with ploidy and taxonomy ( Berdugo-Cely et al., 2017 ; Hardigan et al., 2017 ; Ellis et al., 2018 ; Berdugo-Cely et al., 2021 ). This discrimination agrees with our results, in which ploidy and taxonomy explained the identified genetic groups.…”
Section: Discussionmentioning
confidence: 99%
“…We tested if there was population differentiation by calculating the F ST and the percentages of differentiation between and within identified subpopulations using the analysis of molecular variance (AMOVA) in the R-packages dartR ( Mijangos et al., 2022 ) and Poppr ( Kamvar et al., 2014 ), respectively. Finally, we manually estimated the genetic diversity by calculating the observed heterozygosity (Ho) per genotype and genetic group, using the methodology described by Berdugo-Cely et al. (2021) .…”
Section: Methodsmentioning
confidence: 99%